Synergistic protective effect of carboxymethyl chitosan and cathodic protection of X70 pipeline steel in seawater. Issue 6 (13th January 2017) - Feng, Panpan; Wan, Kai; Cai, Guowei; Yang, Lihui; Li, Yantao
Abstract : This study has investigated corrosion inhibition performance on X70 pipeline steel in seawater using carboxymethyl chitosan (CMCS) and Na2 WO4 at a cathodic protection potential of −0.85 V ( vs. SCE). Abstract : This study has investigated corrosion inhibition performance on X70 pipeline steel in seawater using carboxymethyl chitosan (CMCS) and Na2 WO4 at a cathodic protection potential of −0.85 V ( vs. SCE). The corrosion behaviors were studied using electrochemical methods, scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). The results show that the inhibition efficiency increases when the CMCS concentration increases. Polarization curves reveal that CMCS and Na2 WO4 exhibit a nice synergy for the corrosion inhibition of X70 pipeline steel in seawater. The inhibition mechanism behind the synergistic protective effect of CMCS and Na2 WO4 is assumed to occur via both chemisorption on the steel surface through the active sites in the molecule and physisorption. When combined with cathodic protection, corrosion can be inhibited and calcareous deposits cannot form on the surface.